Social interaction, support preferences, and the use of wearable health trackers - Pennington, Natalie; Dam, Linda (Frontiers in Communication, 2023)
Introduction Drawing on uses and gratifications theory, social cognitive theory, and related work, this research assessed how social factors relate to reported weekly use and behavioral intentions toward the use of wearable health trackers (WHT). Methods Through two studies we surveyed current users of WHT, including smartwatches, to better understand what factors encouraged engagement. Study One (N = 333) consisted of a college student sample. Study Two (N = 319) was conducted through an online panel from Prolific. Results For Study One, results suggested that connection, social comparison, and one's comfort with seeking support predicted weekly use, while need for support was a negative predictor of device use. In terms of behavioral intentions, connection and one's comfort with seeking support remained positive predictors. For Study Two, only one's comfort with seeking support predicted weekly use, while one's comfort with seeking support and social sharing both predicted behavioral intentions. Additional analysis in Study Two comparing users of dedicated WHT and smartwatches also found differences in terms of behavioral intentions and social sharing. Discussion Collectively, the two studies offer insight into what social factors contribute to the use of WHT, including evidence that one's need for support for exercise may serve as a barrier to WHT use.